Toughened two-component epoxy structural adhesive

By using epoxy resin composition A and a curing agent composition B of the room temperature curing agent and chain expansion agent B in the dual -component segmentation adhesive, the problem of insufficient adhesive toughness and adhesion in the existing technology, Realize high intensity and good adhesion.

CN119343394APending Publication Date: 2025-01-21ZEPHYROS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380045974.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-08
Filing Date
2023-06-08
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing room temperature cured two-component epoxy adhesives perform poorly in high overlap shear strength, T-peel strength and wedge impact peel strength, while poor adhesion on metals contaminated by lubricants.

Method used

A dual -component adhesive containing epoxy resin composition A and curing agent composition B, of which the curing agent composition B contains at least one room temperature curing agent and at least one of each molecule. Chain to improve the toughness and adhesion of the adhesive.

Benefits of technology

The dual-composition oxygen adhesive that is solidified at room temperature has high overlap shear strength, T-peeling strength, and wedge-shaped impact peeling strength, and shows good adhesion on the metal contaminated by the lubricant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343394A_ABST
    Figure CN119343394A_ABST
Patent Text Reader

Abstract

A two-component room temperature curing adhesive comprising an epoxy resin composition A and a curing agent composition B wherein the curing agent composition B comprises at least one room temperature curing agent and at least one chain extender having at least two reactive groups per molecule.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Priority claim

[0002] This application claims the benefit of the filing date of U.S. Provisional Application Serial No. 63 / 350,079, filed on June 8, 2022. The contents of that application are incorporated herein by reference in their entirety for all purposes. Technical Field

[0003] The present teachings are generally directed to a two-component epoxy adhesive that cures at room temperature and provides an excellent combination of high lap shear strength, T-peel strength, and wedge impact resistance, as well as good adhesion to metals contaminated with lubricants. Background Art

[0004] Epoxy adhesives are widely used in industry for initial assembly structures and repair purposes. Single-component adhesives contain latent curing agents and can be activated by heat or another stimulus to initiate polymer advancement and subsequent polymerization and / or crosslinking. Curing at elevated temperatures (i.e. 150-200° C.) helps crosslinked networks and potential high strength. The heat-induced phase separation of toughening agents (e.g., toughening agents) allows high toughness as indicated by impact resistance or peel resistance or fracture toughness. In addition, heat application can help improve the adhesion to certain contaminated surfaces (e.g., those surfaces contaminated by oil or grease), where heat can help displace or dissolve contaminants. However, single-component heat-activated adhesives cannot be used in all applications. For example, lightweight materials (e.g., aluminum, carbon composites) have been widely used in the automotive industry to reduce weight and improve fuel efficiency. Due to different coefficients of thermal expansion (CTE), these lightweight materials expand and contract differently relative to steel as the temperature changes. When materials with different CTEs are bonded together by adhesives, the bonded structure deforms as the adherend undergoes heating and cooling cycles. It is well known that internal stress caused by deformation can reduce adhesion durability and pose challenges for combining dissimilar materials.

[0005] Compared to many heat-activated adhesives, room temperature curable (RTC) adhesives include two components - typically a resin component A and a curing agent component B. The curing process begins with mixing the two components at room temperature. When such adhesives are used to bond dissimilar materials, minimal deformation occurs due to the absence of metal expansion and contraction due to exposure to temperature changes during the bonding process. These adhesives are also better suited to meet the growing interest in low temperature curing systems (i.e., 100°C or lower) and in application environments where heat curing is not possible or convenient (e.g., during automotive body repair). Due to the latency of the curing agent in a one-component heat-activatable adhesive, it is difficult or impossible to achieve a suitably high degree of cure at temperatures below 100°C.

[0006] Unfortunately, despite the aforementioned advantages of RTC adhesives, matching the performance of heat-activatable one-part epoxy adhesives has been difficult. In particular, two-part materials typically have poor toughness (e.g., low peel and impact resistance) and often have poor adhesion on metals with contaminants (e.g., stamping oils) due to higher viscosity and hindered wetting at room temperature.

[0007] EP2658939 describes a structural adhesive film comprising a combination of thiol and polyamine curing agents. However, the film is formulated to undergo a two-stage curing process, one of which requires additional heat to activate the latent curing agent. Thus, a room temperature curing formulation having a combination of improved physical properties as described herein is neither described nor contemplated.

[0008] Therefore, the present teachings seek to provide a room temperature curing epoxy adhesive that simultaneously has high lap shear strength, improved T-peel strength and impact peel strength, and enhanced adhesion on lubricant-contaminated metals compared to existing two-component adhesives of materials. Summary of the invention

[0009] The teachings herein relate to a two-component adhesive comprising an epoxy resin composition A and a curing agent composition B, wherein the curing agent composition B comprises at least one room temperature curing agent and at least one chain extender having at least two reactive groups per molecule to promote a cured adhesive having a structure that more closely mimics that of a thermoplastic. The epoxy resin composition A may contain an epoxy / elastomer adduct and the curing agent composition B may contain an amine-terminated elastomer.

[0010] The epoxy resin composition A and / or the curing agent composition B may contain a phenol-terminated urethane toughening agent.

[0011] The epoxy resin composition A may contain a diacid adduct.

[0012] The adhesive may have a T-peel strength of at least 6 N / mm when cured at 23°C for 7 days when measured at a crosshead speed of 254 mm / min and a 0.25 mm bond line.

[0013] The adhesive may have a lap shear strength greater than 20 MPa when cured at 23°C for 7 days when measured in accordance with ASTM D5868 at a 50.4 mm / min crosshead speed and a 0.25 mm bond line.

[0014] The adhesive may have a wedge impact peel strength greater than 21 N / mm when cured at 23°C for 7 days when measured in accordance with ISO 11343 at a 2 m / s test rate and a 0.25 mm bond line.

[0015] Curing agent composition B may include a difunctional chain extender in a range of about 0.5 wt % to about 30 wt %.

[0016] Curing agent composition B may include about 0.5 wt % to about 90 wt % of a multifunctional room temperature curing agent.

[0017] The adhesive may include the epoxy / elastomer adduct in the range of about 1 wt % to about 60 wt % of the epoxy resin composition A.

[0018] Curing agent composition B may contain the amine terminated elastomer in the range of about 2% to 40%.

[0019] The binder may include an epoxy / diacid adduct present in an amount of about 0.2 wt % to about 25 wt %, or even about 6 wt % to about 10 wt % of the epoxy resin composition A.

[0020] The adhesive may include a toughening agent in an amount ranging from about 2 wt % to about 50 wt % of the epoxy resin composition A and / or the curing agent composition B.

[0021] The binder may include polymer particles present in an amount of at least about 3 wt % but less than about 60 wt %, or even at least about 10 wt % but less than about 32 wt % of the epoxy resin composition A.

[0022] The binder may include a phenoxy group dissolved in the epoxy resin in an amount ranging from about 0.5 wt % to about 10 wt % of the epoxy resin composition A.

[0023] The adhesive may include a difunctional chain extender selected from a monoprimary amine selected from 1-naphthylamine, 2-naphthylamine, ethanolamine, phenylethylamine, oleylamine, a dithiol such as 2,2'-(ethylenedioxy)diethanethiol and 1,2-ethanedithiol, or any combination thereof. The adhesive may include a room temperature curing agent selected from an amine, an amine derivative, a polyamide, a thiol or a thiol derivative, or any combination thereof.

[0024] The elastomer in the epoxy / elastomer adduct may be selected from ATBN, CTBN, ETBN, polysulfide, epoxide-terminated siloxane monomers or oligomers, or any combination thereof. The adhesive may include an epoxy / diacid adduct, wherein the diacid component is selected from C18 diacid, C36 diacid, or any combination thereof.

[0025] The toughening agent or the toughening agent in the adduct combined with the epoxy resin may be selected from phenol-terminated urethane, Epoxonic 328, or any combination thereof.

[0026] The polymer particles may include a core modifier of polybutadiene, styrene-butadiene rubber, or a combination thereof. The polymer particles may include core / shell rubber particles having an average size of about 100-200 nm. The polymer particles may be substantially free of agglomerated particles.

[0027] The adhesive may include one or more reinforcing components. The adhesive may include one or more reinforcing components selected from silicon dioxide, diatomaceous earth, glass, clay, nanoclay, glass beads or bubbles, glass, carbon or ceramic fibers, nylon, aramid or polyamide fibers, pyrophyllite, sauconite, saponite, nontronite, wollastonite, montmorillonite or any combination thereof. The adhesive may include silicon dioxide and / or calcium-based reinforcing components. The adhesive may include a silicon dioxide-based reinforcing component comprising fumed silica.

[0028] The adhesive may be substantially free of any components requiring heating to activate.The adhesive may have a sufficient thickness of at least 0.2 mm, making it thicker than a film adhesive.

[0029] The adhesive materials described herein provide similar physical properties to heat-cured structural adhesives, but are instead two components that are combined and cured at room temperature (eg, 20° C.-25° C.).

[0030] The teachings herein also include a two-component adhesive comprising an epoxy resin composition A and a curing agent composition B, wherein the curing agent composition B comprises at least one room temperature curing agent and at least one chain extender, wherein the room temperature curing agent is selected from an amine, an amine derivative, a polyamide, a thiol or a thiol derivative, or any combination thereof, and the chain extender has at least two reactive groups per molecule: 1-naphthylamine, 2-naphthylamine, ethanolamine, phenylethylamine, oleylamine, a dithiol such as 2,2'-(ethylenedioxy)diethanethiol and 1,2-ethanedithiol, or any combination thereof.

[0031] The teachings herein also relate to a composite material, comprising a first material layer and a second material layer, wherein the first material layer comprises an aluminum material or a polymer material, and the second material layer comprises an aluminum material or a polymer material, wherein the first material layer is bonded to the second material layer with a two-component adhesive, and the adhesive comprises an epoxy resin composition A and a curing agent composition B; wherein the curing agent composition B comprises at least one room temperature curing agent, and the room temperature curing agent is selected from amines, amine derivatives, polyamides, thiols or thiol derivatives, or any combination thereof; and at least one chain extender having at least two reactive groups per molecule: 1-naphthylamine, 2-naphthylamine, ethanolamine, phenylethylamine, oleylamine, dithiols such as 2,2'-(ethylenedioxy)diethanethiol and 1,2-ethanedithiol, or any combination thereof.

[0032] The binder may include a diacid / epoxy adduct including about 1:6 to 6:1 parts of diacid to epoxy, more preferably about 1:4 to 4:1 parts of diacid to epoxy.

[0033] The teachings herein also contemplate vehicle structures incorporating the composite materials disclosed herein.

[0034] The teachings herein also relate to the use of the composite materials disclosed herein in transportation vehicles.

[0035] The teachings herein also relate to using the adhesives described herein to bond two dissimilar materials.

[0036] The teachings herein also relate to using the adhesives described herein to bond two similar materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The glass transition temperature (T) of exemplary materials according to the present teachings as determined by dynamic mechanical analysis is shown. g ). DETAILED DESCRIPTION

[0038] The explanation and description presented herein are intended to make other technical personnel in the art familiar with this teaching, its principles and its practical application. The specific embodiments of this teaching set forth are not intended to be exhaustive or limit this teaching. The scope of this teaching should be determined with reference to the full scope of the equivalents given by the attached claims and these claims. The disclosures of all articles and references (including patent applications and publications) are incorporated herein by reference for all purposes. Other combinations such as will be collected from the following claims are also possible, which are also incorporated in this written description by reference. Unless otherwise stated, the percentages herein refer to weight percentages.

[0039] The materials of the present teachings can be applied to various articles for adding structural integrity to parts or members of the articles. Examples of such articles include, but are not limited to, household or industrial appliances, furniture, storage containers, buildings, structures, etc. The materials can be applied to parts of transportation vehicles, including ships, trucks, trains, airplanes, motor vehicles, etc. The materials can be used in motor vehicles, for example, for use with the body or frame members (e.g., vehicle frame rails) of a motor vehicle.

[0040] The present teachings relate to increased plastic properties of adhesives relative to what has been accomplished in the prior art, phase separation toughening agents, and matrix toughening for high toughness in room temperature curing epoxy adhesives.

[0041] The cross-linking density that reduces can contribute to the plasticity property that increases and the local plastic deformation that strengthens, and this can promote the cohesive failure and the local yield of adhesive.When fracture makes crack propagation by adhesive, cohesive failure takes place, and stays adhesive layer on two adherends.Usually, compared with the failure (adhesive failure) at the interface between adhesive and adherend, it provides the energy absorption of improvement.This is why cohesive failure is usually associated with high impact resistance, although independent cohesive failure can not realize this point.Usually need to have the material with lower cross-linking density to improve failure strain, particularly if need to produce the material that will yield.

[0042] One method of introducing plastic properties is to use a chain extender, a small molecule with two functional groups (e.g., reactive hydrogen) that reacts with the epoxy resin to extend the linear chain length of the epoxy resin molecule to help impart thermoplastic-like properties. In contrast to multifunctional curing agents, chain extenders promote more plastic properties, presumably enabling local relative translation of the molecules, and can reduce the internal strength of the adhesive, increasing the likelihood of obtaining cohesive failure of the material. Chain extenders have been found to improve the toughness of heat-activated adhesives when at least 50% of the epoxy resin is chain extended (see U.S. Pat. No. 6,486,256). Thus, a high degree of chain extension and a low degree of crosslinking can reduce the glass transition temperature (Tg) of the resulting material. g Due to the glass transition effect, room temperature curing adhesives have a characteristically lower T than heat activated materials. g Therefore, the use of high dosages of chain extenders in room temperature curing adhesives makes it possible to achieve a reasonable T g In addition, high dosages of chain extenders slow down the curing of adhesives due to their lower functionality compared to common multifunctional curing agents. The resulting extended curing time is problematic for certain applications.

[0043] In the present teachings, low percentages of chain extenders can be used in combination with other curing agents to modify the toughness of the material while maintaining a reasonable T gand cure speed. Examples of chain extenders include monoprimary amines, disecondary amines, and dithiols. As a non-limiting example, monoprimary amines may include 1-naphthylamine, 2-naphthylamine, ethanolamine, phenylethylamine, oleylamine, or a combination thereof. Examples of suitable dithiols include DMDO (2,2'-(ethylenedioxy)diethylmercaptan) from Arkema Innovative Chemistry and Thiocure GDMP ((ethylene glycol bis(3-mercaptopropionate)) from Bruno Bock. The chain extender may be included in an amount of up to about 10% by weight of the curing agent composition. The curing agent may be about at least about 0.2% by weight, more typically at least about 1% by weight, and more typically at least about 2% by weight. The curing agent may be about 30% by weight or less of the curing agent composition, more typically about 10% by weight or less, more typically about 7% by weight or less, and even more typically 5% by weight or less.

[0044] The epoxy resin composition may additionally include a high molecular weight polymer, such as a phenoxy resin, to increase the thermoplastic properties of the adhesive. Phenoxy resins are high molecular weight thermoplastic condensation products of bisphenol-A and epichlorohydrin and its derivatives. Phenoxy resins that may be used have the following basic formula:

[0045]

[0046] Wherein, n is generally 30 to 100, preferably 50 to 90. Modified phenoxy resins may also be used. Examples of phenoxy resins that may be used are products sold by Gabriel Performance Products. Examples of suitable materials are PKHB, PKHC, PKHH, PKHJ, PKHP pellets and powders. Alternatively, phenoxy / polyester mixtures and epoxy / phenoxy mixtures may be used. In order to enhance the compounding of the adhesive, the phenoxy resin is preferably supplied to the mixed composition as a solution. Although any solvent may be used to reduce the incorporation temperature during mixing, it is particularly preferred to use a low molecular weight epoxy resin as a solvent because it may be a reactive component in the adhesive and improves mechanical properties when activated.

[0047] Phase separation materials can be included in the epoxy resin composition A or the curing agent composition B, depending on the mutual chemical stability of the components. These materials, if partially soluble in the binder matrix, impart flexibility and increase the ability to absorb energy during plastic deformation. Therefore, these materials can be included to change the structural properties of the material, such as strength, failure strain, fracture toughness (G 1C ), peel, bond durability, stiffness or other properties.

[0048] For example, polythiol (also known as polythiol) can be included in the curing agent composition B as a curing agent and / or a chain extender. Polythiol curing agents not only accelerate curing but also improve T-peel strength. However, polythiol exhibits low compatibility with cured epoxy resins and can phase separate into different domains from the epoxy matrix. When 60% polythiol is mixed with 40% epoxy resin, two different glass transition temperatures (i.e., -48.5°C and 80.5°C, see Figure 1 ). It was found that these separated domains promote cohesive failure of the adhesive and the resulting high peel strength. At an optimal ratio of polyamide curing agent to thiol curing agent, a T-peel strength of about 9 N / mm can be achieved. Examples of difunctional and multifunctional thiol curing agents include products from Gabriel Performance Products and and products from Bruno Bock and Thiokol TM and The polysulfide of curing agent composition B is present in an amount of up to 95% by weight of curing agent composition B. It may be about at least about 2% by weight, more typically at least about 10% by weight, more typically at least about 30% by weight. It may be about 95% by weight or less of curing agent composition B, more typically about 80% by weight or less, more typically about 75% by weight or less, and even more typically 60% by weight or less.

[0049] Curing agent composition B may also include a phase separated amine-terminated elastomer. Examples of amine-terminated elastomers may be amine-terminated liquid rubber (ATBN) from Huntsman Advanced Materials (e.g., Hypro 1300X16 ATBN). The amine-terminated elastomer is typically less than 50% by weight of the curing agent composition, more typically less than 35% by weight of the curing agent composition, and may even be less than 20% by weight of the curing agent composition, although higher and lower values ​​are possible unless otherwise stated.

[0050] The phase separation material can be contained in the epoxy resin composition A as an adduct of an epoxy resin. Examples of preferred adducts or preferred components for producing adducts are epoxidized polysulfide polymers, such as those sold under the trade name Thioplast TM G and Thioplast TM EPS is sold as a product. A particularly preferred grade is Thioplast available from Akzo Nobel TM G10 and Thioplast TM EPS-80. Another example is available from Emerald Performance Commercially available Hypro TM 1300X13NA (CTBN), which may be adducted with the diglycidyl ether of bisphenol-F, the diglycidyl ether of bisphenol-A, or any other suitable diepoxide. Another example of a preferred epoxy / elastomer adduct is Hypro TM 1300X63 (ETBN (butadiene glycidyl ester and butadiene-acrylonitrile)).

[0051] The adduct may be included in an amount of up to about 75% by weight of the epoxy resin composition A. The adduct may be about at least about 5% by weight, more typically at least about 20% by weight, more typically at least about 40% by weight. The adduct may be about 75% by weight or less of the epoxy resin composition, more typically about 70% by weight or less of the epoxy resin composition, more typically about 65% by weight or less of the epoxy resin composition, and even more typically 60% by weight or less of the epoxy resin composition. The adduct may be a combination of two or more specific adducts. The adduct may be a solid adduct, a liquid adduct, or a semisolid at a temperature of 23°C, or some combination thereof.

[0052] Solid adducts are preferred for improving physical properties because higher molecular weight of the adducts has been shown to enhance adhesive properties including peel strength and impact resistance. To incorporate these solid materials into formulations, solutions with liquid epoxy resins as solvents can be prepared as a preferred way to reduce mixing temperatures.

[0053] Toughener can be included in epoxy resin composition A or curing agent composition B, depending on the chemical stability of the toughener. The use of the term toughener can relate to a single toughener or a combination of multiple different tougheners. Although other tougheners can be used, preferred tougheners include epoxy-modified, urethane-modified prepolymers (particularly those of phenol capped) or any combination thereof. It is believed that when a polyurethane toughener is included, the material can show enhanced flexibility and substantially maintain impact strength (e.g., impact resistance) at low temperatures while increasing the glass transition temperature (T g ) is minimized (e.g., compared to other toughening agents). Examples of preferred toughening agents may be toughening agents based on phenolic terminated urethanes, EP 1820 (available from Innovative Resin Systems) and DY965 from Huntsman.

[0054] Examples of other preferred toughening agents are polyurethane modified epoxy resins sold under the trade names GME-3210 and GME-3220, which are commercially available from GNS Technologies. Other examples of preferred toughening agents are epoxy terminated polyethers or amine precursors for preparing epoxy terminated polyethers, such as JEFFAMINE M series or SD series commercially available from Huntsman, DER 732 commercially available from Olin Corporation. Cashew nut shell liquid based toughening agents such as epoxidized liquids Cardolite NC-514 and Cardolite Lite 2513HP are also useful toughening agents. Another example of a toughening agent is Epoxonic 328 adduct. Unless otherwise specified, all individual toughening agents discussed herein can be used alone or in combination with each other in the materials of the present invention.

[0055] Typically, the toughening agent is less than 50 weight percent, more typically less than 35 weight percent, and may even be less than 20 weight percent, although higher and lower values ​​are possible unless otherwise stated.

[0056] The epoxy resin composition A may include an epoxy / diacid adduct. The use of the term diacid may relate to any multifunctional molecule having two carboxylic acid moieties. Some diacid compounds are introduced into the epoxy backbone to reduce the strength or stiffness of the adhesive, thereby improving flexibility and bonding durability after exposure to moisture and corrosion caused by salt solutions due to the hydrophobicity of the adduct. The diacid component of the epoxy / diacid adduct may be a diacid compound of C8-C40 or higher adducted with epoxy. The epoxy component of the epoxy / diacid adduct may be DGEBF (diglycidyl ether of bisphenol F) and DGEBA (diglycidyl ether of bisphenol A). The diacid may be saturated or unsaturated. Preferably, the diacid is derived from an unsaturated fatty acid. Examples of preferred epoxy / diacid adducts are The esterification product of YDF-172LV (DGEBF) and C18 diacid. Other examples of preferred epoxy / diacid adducts are available from Emerald Performance DA323 (DGEBA and dimer fatty acid adduct) from Kukdo Chemical Co., Ltd. and Epokukdo YD-172 from Kukdo Chemical Co., Ltd.

[0057] The adduct typically includes about 1:6 to 6:1 parts of diacid to epoxy, more preferably about 1:4 to 4:1 parts of diacid to epoxy. More typically, the adduct includes at least about 10%, more typically at least about 20%, even more typically at least about 40% of the diacid, and typically includes less than or equal to about 60% of the diacid, although higher or lower percentages are possible.

[0058] Generally, the epoxy resin composition preferably includes at least one type of polymer particles. Such polymer particles can be used to improve fracture toughness (G 1C ), peel resistance, and impact resistance. As used herein, the term "polymer particles" is defined as particles comprising a polymer material. As with any other component of the present teachings, the term "polymer particles" may include one or more polymer particles. A variety of polymer particles may be used in the practice of the present teachings, and typically include one or more elastomers. It is generally preferred that the polymer particles are at least 4%, more typically at least 7%, even more typically at least 10%, still more typically at least 13%, even more typically at least 16% of the weight of the activatable material, and it is also preferred that the polymer particles are less than 90% of the weight of the activatable material, more typically less than 40% of the weight of the activatable material, and even more typically less than 30% of the weight of the activatable material, although higher or lower amounts may be used in particular embodiments.

[0059] Examples of useful polymer particles include, but are not limited to, particles suspended in a liquid epoxy resin sold under the trade name KaneAce TM Sold and commercially available from KanekaAmericas Holding Co., Ltd. KaneAce TM Particularly preferred grades are sold under the trade names MX-134 and MX-267. The size of the polymer particles may be on average greater than or equal to 50 nm and less than or equal to 300 nm.

[0060] The curing agent composition B may comprise at least one polyamine and a polyamide curing agent (e.g., and ). Certain curing agents such as Ancamide 910, which are intended to impart flexibility, also improve the toughness of the adhesive. The polyamide curing agent may be included in an amount of up to about 95% by weight of the curing agent composition B. It may be about at least about 30% by weight, more typically at least about 40% by weight, and more typically at least about 50% by weight. It may be about 95% by weight or less of the curing agent composition B, more typically about 80% by weight or less of the curing agent composition B, more typically about 75% by weight or less of the curing agent composition B, and even more typically 60% by weight or less of the curing agent composition B.

[0061] The epoxy resin compositions described herein may include one or more epoxy resins. Epoxy resins may be added to increase adhesion, optimize rheological behavior, and / or provide strength to the material. An exemplary epoxy resin may be a phenolic resin, which may be a novolac type or other type of resin. An example of a suitable epoxy resin is available from AdityaBirla YDF 172LV (DGEBF). Other preferred epoxy-containing materials may include modified epoxy resins. The epoxy resin may be a silane-modified epoxy resin or a silane-free epoxy resin. For example, a silane-modified epoxy resin may help to allow the material to adhere to non-ferrous metals, such as aluminum. The silane-modified epoxy resin may be a reaction product between at least one epoxy resin and a silane compound. An example of a suitable silane-modified epoxy resin is Epokukdo KSR-177 (bifunctional silane-modified epoxy resin) purchased from Kukdo Chemical. In addition, various mixtures of several different epoxy resins may also be used. The epoxy resin may be present in other formulation components (e.g., epoxy / elastomer adducts, polymer particle dispersions, and epoxy / diacid adducts). The concentration and type of epoxy resin present in the formulation components vary according to the manufacturer and specific grade. The epoxy resin may be present in the formulation components as an adduct, unreacted epoxy resin, or both.

[0062] The epoxy resin composition A and the curing agent composition B may contain fillers. The fillers may be organic or inorganic additives different from the polymer matrix to improve the adhesion properties, change the thixotropic properties and / or improve moisture resistance. These organic or inorganic additives include, for example, those sold under the trade name and Silicates, mica, talc, clay, sold under the trade name and Wollastonite, calcium carbonate, calcium oxide, calcium sulfate, sold under the trade name and Fumed silica, hollow glass and polymer spheres, carbon black and graphite are sold. Other additives, reagents or performance modifiers can also be included in the material as needed, including but not limited to anti-UV agents, flame retardants, heat stabilizers, colorants, processing aids, lubricants, etc.

[0063] The specific combination and relative amount of one or more materials described herein can help provide improved values ​​for one or more of T-peel strength, wedge impact peel strength and / or lap shear strength. As an example, the combination of polyamide and polythiol curing agent can provide high T-peel strength. At the appropriate ratio of polyamide and thiol curing agent, a T-peel strength of about 9N / mm can be achieved. The ratio of thiol and polyamide can be selected based on the required mechanical properties and curing time of the target application. As another example, the combination of elastomer adduct, toughener and diacid adduct in epoxy resin composition A can help achieve high impact peel strength. The synergistic effect of these ingredients can be explained by a combination of phase separation toughening, matrix flexibility, local plastic deformation and reduced internal strength. For example, it has been found that diacid adduct reduces the strength of the adhesive, promotes cohesive failure and improved mechanical properties. Elastomer adduct can form a phase separation domain for toughening, and toughener improves the flexibility of the adhesive matrix.

[0064] Certain adhesive materials formed according to the present teachings exhibit a tensile modulus greater than about 900 MPa, greater than about 1200 MPa, and possibly even greater than about 3000 MPa when measured according to the ASTM D638 Type IV test method at a crosshead speed of 5 mm / min.

[0065] Certain adhesive materials formed according to the present teachings exhibit lap shear strengths greater than about 10 MPa, greater than about 15 MPa, and even greater than 20 MPa when measured according to ASTM D5868 at a 50.4 mm / min crosshead speed and a 0.25 mm bond line.

[0066] Certain activatable materials formed according to the present teachings exhibit a wedge impact peel strength greater than about 20 N / mm, greater than about 25 N / mm, and even greater than 30 N / mm when measured according to ISO 11343 at a test rate of 2 m / s and a bond line of 0.25 mm.

[0067] Certain activatable materials formed according to the present teachings exhibit T-peel strengths greater than about 5 N / mm, greater than about 7 N / mm, and even greater than 8.5 N / mm when measured using a 254 mm / min crosshead speed and a 0.25 mm bond line.

[0068] Certain activatable materials formed according to the present teachings exhibit a strain to failure greater than about 5%, greater than about 10%, greater than 20%, and even greater than 30%. The strain to failure is measured by performing a tensile test while using an extensometer to record the deformation, which is then used to calculate the material strain.

[0069] Certain adhesive materials formed according to the present teachings have exhibited a glass transition (T) greater than 30 degrees Celsius, greater than 35 degrees Celsius, and even greater than 45 degrees Celsius, when measured by ASTM D7028-07. g ). This test method (known as dynamic mechanical analysis T g or "DMAT g ”) may be different from the glass transition temperature reported by other measurement techniques (i.e., tan delta peak) on the same test specimen. This test method is often used to determine the upper service temperature of a composite material.

[0070] As a specific example, Figure 1 The glass transition temperature (T) of a material containing 60% polythiol and 40% bis-A epoxy resin as determined by dynamic mechanical analysis is shown. g ).

[0071] For illustrative purposes, Table A is prepared below to illustrate four exemplary formulations for forming room temperature curing adhesives.

[0072] Table A

[0073]

[0074]

[0075] *0.030" EG60, test speed: 254mm / min, bonding line 0.25mm; **0.060" EG60, test speed: 50.4mm / min, bonding line 0.25mm; ***0.030" EG60, test speed: 2m / s, drop weight 25kg, bonding line 0.25mm; ASTM D7028-07. Curing schedule: 7 days at 23°C.

[0076] The adhesives shown in Table A are room temperature curing adhesives characterized by high toughness. While maintaining a lap shear strength above 20 MPa, these adhesives have a T-peel strength above 6 N / mm and a wedge impact peel strength above 20 N / mm. Sample 2, which does not contain a thiol curing agent, shows a T-peel strength above 6 N / mm and a wedge impact peel strength above 30 N / mm. Sample 4 shows a T-peel strength of 8.9 N / mm, which is better than some heat activated adhesives. These results show that the combination of ingredients in the present teachings produces a toughened room temperature curing adhesive with high impact resistance and peel resistance.

[0077] The comparative examples shown below demonstrate the changes in physical properties based on the inclusion / removal of certain components in the curing agent side of the materials disclosed herein. It is worth noting that when certain curing agents (components) are reduced or excluded, the amounts of other curing agents (components) are adjusted to maintain the same stoichiometric ratio.

[0078] Table B

[0079]

[0080]

[0081] *0.030" EG60, test speed: 254mm / min, bond line 0.25mm; **0.060" EG60, test speed: 50.4mm / min, bond line 0.25mm; ***0.030" EG60, test speed: 2m / s, drop weight 25kg, bond line 0.25mm. Curing schedule: 7 days at 23°C; ASTM D7028-07.

[0082] It has been found that the addition of one or more chain extenders to Curing Agent Composition B is key to improving toughness when the adhesive is cured for 7 days at room temperature. Samples 5 and 6 (without or with reduced amounts of chain extenders) exhibit large reductions in physical properties compared to Sample 1, including poor performance in T-peel strength, impact peel strength, and lap shear strength. On the other hand, increasing the amount of chain extender above the control concentration (Sample 7) can also result in reduced lap shear strength compared to Sample 1 due to reduced crosslink density. These results indicate an optimal concentration of chain extender for best overall performance. In addition, the combination of a polyamide curing agent and a mercaptan has been shown to improve the T-peel strength and wedge impact peel strength of the resulting adhesive. As shown in Table B, Sample 8 (without mercaptan) exhibits reduced T-peel strength and wedge impact peel strength compared to Sample 1.

[0083] Table C

[0084]

[0085]

[0086] *0.030" EG60, test speed: 254mm / min, bond line 0.25mm; **0.060" EG60, test speed: 50.4mm / min, bond line 0.25mm; ***0.030" EG60, test speed: 2m / s, drop weight 25kg, bond line 0.25mm; ****0.3MPa lap shear strength. Curing protocol: 7 days at 23°C.

[0087] The ratio of polyamide and mercaptan curing agent plays an important role in determining the physical properties of adhesives, especially lap shear, peeling and impact resistance. Since it is known that polyamide curing agent 2 improves adhesive toughness, in order to prove how mercaptan affects peeling and impact resistance, polyamide curing agent 2 is kept constant in all samples. As shown in Table C, samples 3, 4 and 9-11 contain different percentages of mercaptan. With the increase of mercaptan content, the physical properties including lap shear strength, T peel strength and impact peel strength increase first and then decrease. For example, sample 4 with about 20% mercaptan in the curing agent composition shows the highest lap shear strength (i.e., 21.9MPa), T peel strength (i.e., 8.9N / mm) and wedge impact peel resistance (i.e., 26.4N / mm). The further increase of mercaptan leads to the reduction of these properties. For sample 11 with 49% mercaptan in curing agent composition B, lap shear strength and impact peel strength are reduced to 7.1MPa and 17.3N / mm respectively. The present teachings show that polythiols can be used not only to accelerate cure speed, but can also be used in combination with polyamide and chain extenders to improve adhesion properties. The ratio of thiol to polyamide can be selected based on the target mechanical properties and cure time. However, as expected, increasing the percentage of thiol does continue to reduce open time and fixture time.

[0088] Table D

[0089]

[0090]

[0091] *0.030" EG60, test speed: 254mm / min, bonding line 0.25mm; **0.060" EG60, test speed: 50.4mm / min, bonding line 0.25mm; ***0.030" EG60, test speed: 2m / s, drop weight 25kg, bonding line 0.25mm; ASTM D7028-07. Curing schedule: 7 days at 23°C.

[0092] The combination of elastomer adducts, toughening agents, thermoplastics and diacid adducts is critical for achieving excellent adhesive properties, particularly impact resistance. Table D shows how to exclude these ingredients to affect the mechanical properties of the resulting adhesive. Sample 2 includes all components and shows the best overall performance and maximum wedge impact peel strength and energy. Sample 13 does not include CTBN adducts, thereby showing reduced lap shear strength, T peel strength, wedge impact peel strength and energy. Samples 14 and 12 do not contain polysulfide adducts and urethane toughening agents respectively. Both show reduced lap shear strength, T peel strength, wedge impact peel strength and energy. Samples 15 and 17 that do not contain epoxy adduct toughening agents and phenoxy resins show reduced T peel strength and impact peel strength. Sample 16 does not contain diacid adducts, thereby showing lower T peel strength, wedge impact peel strength and energy. This result proves the synergistic effect of these ingredients on the physical properties of the adhesive.

[0093] Table E

[0094] Sample 2 Fusor 2098 Scotch Weld DP420 Black Sikapower 1277 Manufacturer L&L Dow and Lord 3M Sika Lap shear strength*(MPa) 9.8 0.9 0 6.0

[0095] *0.060”EG60, 0.39-0.46mg / cm 2 Lubricant 61MALHCL, test speed: 50.4mm / min, bonding line 0.25mm.

[0096] Certain adhesive materials formed according to the present teachings exhibit improved adhesion on lubricant-contaminated metals. Sample 2 showed improved adhesion at 0.39-0.46 mg / cm2 compared to three commercial competitive products. 2 Ferrocote 61MAL·HCl showed much higher lap shear strength on EG60 coated. This result shows that the adhesive of the present teaching can allow for no or minimal cleaning of metal adhesives, which can provide significant advantages in manufacturing facilities. In addition, in cases where metal cleaning is insufficient, the adhesive of the present invention can ensure improved bond strength compared to competitive products.

[0097] As used herein, unless otherwise stated, the present teachings contemplate that any member of a genus (list) can be excluded from the genus; and / or any member of a Markush group can be excluded from the group.

[0098] Unless otherwise stated, any numerical value described herein includes all values ​​from the lower limit to the upper limit with one unit as increment, provided that there is an interval of at least 2 units between any lower limit and any upper limit. As an example, if the value of the amount, property or process variable (such as, for example, temperature, pressure, time, etc.) of a component is stated to be, for example, 1 to 90, preferably 20 to 80, more preferably 30 to 70, it is intended that the intermediate range value (such as 15 to 85, 22 to 68, 43 to 51, 30 to 32, etc.) is within the teaching of this specification. Similarly, each intermediate value is also within this teaching. For a value less than 1, as the case may be, a unit is considered to be 0.0001, 0.001, 0.01 or 0.1. These are only examples of specific intent, and all possible combinations of the numerical values ​​between the minimum value and the maximum value listed should be considered to be clearly stated in a similar manner in this application. It can be seen that the teaching of the amount represented as "parts by weight" herein also considers the same range represented by weight percentage. Thus, a statement in terms of "'x' parts by weight of the resulting polymer blend composition" with a range also contemplates teaching of a range of the same recited amount of "x" as a weight percent of the resulting polymer blend composition.

[0099] Unless otherwise specified, all ranges include both endpoints and all numbers between the endpoints. The use of "about" or "approximately" in connection with a range applies to both ends of the range. Thus, "about 20 to 30" is intended to cover "about 20 to about 30", including at least the specified endpoints.

[0100] The disclosures of all articles and references (including patent applications and publications) are incorporated herein by reference for all purposes. The term "consisting essentially of" used to describe a combination shall include the identified elements, ingredients, components, or steps, as well as such other elements, ingredients, components, or steps that do not substantially affect the basic and novel features of the combination. The use of the terms "comprising" or "including" to describe a combination of elements, ingredients, components, or steps herein also encompasses embodiments consisting of or consisting essentially of elements, ingredients, components, or steps.

[0101] Multiple elements, ingredients, components or steps can be provided by a single integrated element, ingredient, component or step. Alternatively, a single integrated element, ingredient, component or step can be divided into separate multiple elements, ingredients, components or steps. The disclosure of "one" or "an" describing an element, ingredient, component or step is not intended to exclude additional elements, ingredients, components or steps.

[0102] It should be understood that the above description is intended to be illustrative rather than restrictive. After reading the above description, many embodiments and many applications other than the examples provided will be apparent to those skilled in the art. Therefore, the scope of the present invention should not be determined with reference to the above description, but should be determined with reference to the full scope of the equivalents given by the appended claims and these claims. The disclosures of all articles and references (including patent applications and publications) are incorporated herein by reference for all purposes. The omission in the following claims of any aspect of the subject matter disclosed herein is not a waiver of such subject matter, nor should it be considered that the inventor does not consider such subject matter to be a part of the disclosed inventive subject matter.

Claims

1. A two-component adhesive comprising: i) epoxy resin composition A; and ii) a curing agent composition B, wherein: The curing agent composition B comprises: a) at least one room temperature curing agent; b) at least one chain extender having at least two reactive groups per molecule; The epoxy resin composition A contains epoxy / elastomer adduct, and the curing agent composition B contains amine-terminated or thiol-terminated elastomer.

2. The adhesive according to claim 1, wherein The epoxy resin composition A and / or the curing agent composition B contain a phenol-terminated urethane toughening agent.

3. The adhesive according to claim 1 or claim 2, wherein: The epoxy resin composition A comprises a diacid adduct.

4. An adhesive according to any one of the preceding claims, wherein The adhesive has a T-peel strength of at least 6 N / mm when cured at 23°C for 7 days when measured at a crosshead speed of 254 mm / min and a 0.25 mm bond line.

5. An adhesive according to any one of the preceding claims, wherein The adhesive has a lap shear strength greater than 20 MPa when cured at 23°C for 7 days when measured in accordance with ASTM D5868 at a 50.4 mm / min crosshead speed and a 0.25 mm bond line.

6. An adhesive according to any one of the preceding claims, wherein The adhesive has a wedge impact peel strength greater than 21 N / mm when cured at 23°C for 7 days when measured in accordance with ISO 11343 at a 2 m / s test rate and a 0.25 mm bond line.

7. An adhesive according to any one of the preceding claims, wherein The curing agent composition B includes a difunctional chain extender in a range of about 0.5 wt % to about 30 wt %.

8. An adhesive according to any one of the preceding claims, wherein The curing agent composition B includes a multifunctional room temperature curing agent in a range of about 0.5 wt % to about 90 wt %.

9. An adhesive according to any one of the preceding claims, wherein The adhesive comprises an epoxy / elastomer adduct in the range of about 1 wt % to about 60 wt % of the epoxy resin composition A.

10. An adhesive according to any one of the preceding claims, wherein The curing agent composition B comprises an amine terminated elastomer in the range of about 2% to 40%.

11. An adhesive according to any one of the preceding claims, wherein The adhesive comprises an epoxy / diacid adduct present in an amount of about 0.2 wt % to about 25 wt %, or even about 6 wt % to about 10 wt % of the epoxy resin composition A.

12. An adhesive according to any one of the preceding claims, wherein The adhesive includes a toughening agent in a range of about 2 wt % to about 50 wt % of the epoxy resin composition A and / or the curing agent composition B.

13. An adhesive according to any one of the preceding claims, wherein The binder comprises polymer particles present in an amount of at least about 3 wt % but less than about 60 wt %, or even at least about 10 wt % but less than about 32 wt % of the epoxy resin composition A.

14. An adhesive according to any one of the preceding claims, wherein The adhesive includes a phenoxy group dissolved in an epoxy resin in a range of about 0.5 wt % to about 10 wt % of the epoxy resin composition A.

15. An adhesive according to any one of the preceding claims, wherein The binder comprises a difunctional chain extender selected from 1-naphthylamine, 2-naphthylamine, ethanolamine, phenylethylamine, oleylamine, and dithiols such as 2,2'-(ethylenedioxy)diethanethiol and 1,2-ethanedithiol, or any combination thereof.

16. An adhesive according to any one of the preceding claims, wherein The adhesive comprises a room temperature curing agent, wherein the room temperature curing agent is selected from amines, amine derivatives, polyamides, thiols or thiol derivatives, or any combination thereof.

17. An adhesive according to any one of the preceding claims, wherein The elastomer in the epoxy / elastomer adduct is selected from ATBN, CTBN, ETBN, polysulfide, or any combination thereof.

18. An adhesive according to any one of the preceding claims, wherein The adhesive comprises an epoxy / diacid adduct, wherein the diacid component is selected from a C18 diacid, a C36 diacid, or any combination thereof.

19. An adhesive according to any one of the preceding claims, wherein The toughening agent or the toughening agent in the adduct combined with the epoxy resin is selected from phenol-terminated urethane, Epoxonic 328 or any combination thereof.

20. An adhesive according to any one of the preceding claims, wherein The polymer particles include a core modifier of polybutadiene, styrene-butadiene rubber, or a combination thereof.

21. An adhesive according to any one of the preceding claims, wherein The polymer particles include core / shell rubber particles having an average size of about 100-200 nm.

22. An adhesive according to any one of the preceding claims, wherein The polymer particles are substantially free of agglomerated particles.

23. An adhesive according to any one of the preceding claims, wherein The adhesive includes one or more reinforcing components.

24. An adhesive according to any one of the preceding claims, wherein The adhesive comprises one or more reinforcing components selected from silica, diatomaceous earth, glass, clay, nanoclay, glass beads or bubbles, glass, carbon or ceramic fibers, nylon, aramid or polyamide fibers, pyrophyllite, sauconite, saponite, nontronite, wollastonite, montmorillonite, or any combination thereof.

25. An adhesive according to any one of the preceding claims, wherein The binder includes a silica and / or calcium based reinforcing component.

26. An adhesive according to any one of the preceding claims, wherein The adhesive comprises a silica-based reinforcing component comprising fumed silica.

27. An adhesive according to any one of the preceding claims, wherein The adhesive is substantially free of any components that require heat to activate.

28. An adhesive according to any one of the preceding claims, wherein The adhesive has a sufficient thickness of at least 0.2 mm such that the adhesive is thicker than a film adhesive.

29. A two-component adhesive, wherein: Include: i) epoxy resin composition A; and ii) a curing agent composition B, wherein the curing agent composition B comprises: a) at least one room temperature curing agent selected from amines, amine derivatives, polyamides, thiols or thiol derivatives, or any combination thereof; and b) at least one chain extender having at least two reactive groups per molecule: 1-naphthylamine, 2-naphthylamine, ethanolamine, phenylethylamine, oleylamine, and dithiols such as 2,2'-(ethylenedioxy)diethanethiol and 1,2-ethanedithiol, or any combination thereof.

30. A composite material, wherein: Include: i) a first material layer comprising an aluminum material or a polymer material; ii) a second material layer, the second material layer comprising an aluminum material or a polymer material, wherein the first material layer is bonded to the second material layer using a two-component adhesive, the two-component adhesive comprising: a) epoxy resin composition A; and b) a curing agent composition B, wherein the curing agent composition B comprises: c) at least one room temperature curing agent selected from amines, amine derivatives, polyamides, thiols or thiol derivatives, or any combination thereof; and d) at least one chain extender having at least two reactive groups per molecule: 1-naphthylamine, 2-naphthylamine, ethanolamine, phenylethylamine, oleylamine, and dithiols such as 2,2'-(ethylenedioxy)diethanethiol and 1,2-ethanedithiol, or any combination thereof.

31. The adhesive according to claim 29, wherein: The binder includes a diacid / epoxy adduct containing about 1:6 to 6:1 parts of diacid to epoxy, more preferably about 1:4 to 4:1 parts of diacid to epoxy.

32. A vehicle structure comprising the composite material of claim 30.

33. Use of the composite material according to claim 30 in a transportation vehicle.

34. Use of the adhesive according to claim 1 or claim 29 in bonding two different materials.

35. Use of the adhesive according to claim 1 or claim 29 for bonding two similar materials.

Citation Information

Patent Citations

  • Composition of epoxy resin, chain extender and polymeric toughener with separate base catalyst

    US6486256B1